Analisis Identitas Merek Telkom School Menggunakan Model Prisma Kapferer - Junaedi, Rusli Akhmad (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2025)
Advertising through brand identity is essential for improving the performance of educational institutions (schools) by fostering a strong image through unique, relevant messages tailored to the target audience. This study aims to analyse Telkom School’s brand identity using Kapferer’s Brand Identity Prism Model. The research explores how Telkom School constructs its brand identity through six key facets: physique, personality, culture, relationship, reflection, and self-image. The importance of this study lies in understanding how a strong brand identity can influence stakeholder perceptions and loyalty, particularly within the educational sector. Qualitative descriptive methods were employed, with data collected through interviews, observations, and document analysis from relevant sources. Data from interviews, observations, and documentation were then analysed interpretively using content and thematic analysis. The findings reveal that Telkom School effectively integrates its corporate values and educational mission into its brand identity, creating a distinctive image that resonates with students, parents, and the community. The study concludes that applying Kapferer’s model provides a comprehensive framework for developing and evaluating brand identity strategies. It can reference other educational institutions to strengthen its brand positioning.